2008
DOI: 10.1073/pnas.0712158105
|View full text |Cite
|
Sign up to set email alerts
|

Probing microscopic origins of confined subdiffusion by first-passage observables

Abstract: Subdiffusive motion of tracer particles in complex crowded environments, such as biological cells, has been shown to be widespread. This deviation from Brownian motion is usually characterized by a sublinear time dependence of the mean square displacement (MSD). However, subdiffusive behavior can stem from different microscopic scenarios that cannot be identified solely by the MSD data. In this article we present a theoretical framework that permits the analytical calculation of first-passage observables (mean… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
165
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 193 publications
(171 citation statements)
references
References 51 publications
6
165
0
Order By: Relevance
“…5 The dynamics in such systems is still far from being understood as the experiments indicate the diversity of dynamic behavior and even its origin are being discussed. [6][7][8][9][10][11][12][13][14] The environment in living cells is a good example of such a system. It is mostly heterogeneous, because the motion of molecules is obstructed here by different kinds of lipids and proteins.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…5 The dynamics in such systems is still far from being understood as the experiments indicate the diversity of dynamic behavior and even its origin are being discussed. [6][7][8][9][10][11][12][13][14] The environment in living cells is a good example of such a system. It is mostly heterogeneous, because the motion of molecules is obstructed here by different kinds of lipids and proteins.…”
Section: Introductionmentioning
confidence: 99%
“…15,16 Experimental studies concerning the motion of proteins and lipids in cells were performed using uorescence correlation spectroscopy, [17][18][19][20] pulsed eld gradient NMR 21 and single particle tracking (SPT). 6,7,[22][23][24][25][26][27] In many cases an anomalous diffusion was detected, i.e. the mean square displacement of objects hDr 2 i scaled with time t as hDr 2 i $ t a , with a < 1.…”
Section: Introductionmentioning
confidence: 99%
“…The impact of connectivity on transport properties has been put forward in [8,[23][24][25], where it was found in different examples that transport towards a target node can be favored by a high connectivity of the target, and different functional forms of the dependence of the MFPT on the target connectivity were proposed. On the other hand, the dependence of the MFPT on geometric properties, such as the volume of the network and the source to target distance, has been obtained recently in [26][27][28][29], where it was shown that the starting position of the random walker plays a crucial role in the target search problem. In this context, quantifying the relative importance of distance and connectivity effects on transport properties on complex networks remains an important and widely unanswered question, which can be summarized as follows : is it faster for a random walker to find either a close, or a highly connected target?…”
Section: Introductionmentioning
confidence: 99%
“…The mean squared displacement of a tracer particle is one of the most reliable diagnostics for anomalous transport (21), though it has been argued that even more fundamental measures are required to distinguish anomalous diffusion from other physical processes (22). In the case of axial diffusion of grains in a tumbler (11), due to the opaque nature of the granular materials, measuring individual particle trajectories is a difficult task, which only recently was achieved using high-intensity synchrotron x-rays (23).…”
mentioning
confidence: 99%